2021
DOI: 10.1155/2021/6687589
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of Inula viscosa Extracts on DMBA-Induced Skin Carcinoma Are Mediated by Proteasome Inhibition

Abstract: The aim of this work is to evaluate the antitumor effect mediated by the proteasome inhibitors of Inula viscosa extracts on skin carcinogenesis. Female Swiss albino mice were divided into five groups depending on the combination of skin cancer-inducing 7,12-dimethylbenz(a)anthracene (DMBA) and extract of Inula viscosa treatments. Histology of the affected skin and measurement of proteasome activity were performed to demonstrate the effect of Inula viscosa on mice. The identification of the molecules responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Recently, Yang et al (45) demonstrated that tomentosin induces apoptosis in human leukemia cells via the caspase-facilitated pro-apoptotic pathway, and inhibition of the NF-κB-stimulated Bcl-2. Of note, a recent in vivo study showed the antitumor effects of I. viscosa extract on skin carcinogenesis induced in mice by the inhibition of proteasome activity (46). The ingestion of I. viscosa extract in mice delayed the formation of skin papilloma and reduced their size and numbers (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yang et al (45) demonstrated that tomentosin induces apoptosis in human leukemia cells via the caspase-facilitated pro-apoptotic pathway, and inhibition of the NF-κB-stimulated Bcl-2. Of note, a recent in vivo study showed the antitumor effects of I. viscosa extract on skin carcinogenesis induced in mice by the inhibition of proteasome activity (46). The ingestion of I. viscosa extract in mice delayed the formation of skin papilloma and reduced their size and numbers (46).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a recent in vivo study showed the antitumor effects of I. viscosa extract on skin carcinogenesis induced in mice by the inhibition of proteasome activity (46). The ingestion of I. viscosa extract in mice delayed the formation of skin papilloma and reduced their size and numbers (46).…”
Section: Discussionmentioning
confidence: 99%
“…For the past thirteen years, all studies concerning the anticancer activity of tomentosin have been performed only in vitro on different cell lines (Table 2) [45][46][47][48][49][50][51][52]. Initially, Li and co-workers isolated 13 sesquiterpene lactones (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), from Carpesium faberi, in order to assess their apoptotic and anti-proliferative activities against human breast cancer (MCF-7) cells using the MTT test [46]. They noted that all the molecules, with the exception of tomentosin 17, showed anti-proliferative activities, with IC 50 values varying between 3.0 ± 0.1 and 31.9 ± 1.6 µg/mL.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Plants containing these molecules have already demonstrated tremendous biological effects such as anti-inflammatory, anticancer, antioxidant, and anti-microbial properties in addition to others [8,9]. Recently several correlations have been revealed between the tomentosin content and biological properties which validate the remarkable effects of this molecule, and many recent investigations have highlighted these major pharmacological actions, specifically, anti-inflammatory and anti-cancer properties [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, intracellular proteolysis is involved in the elimination of abnormal proteins, in the supply of amino acids required for the synthesis of novel proteins in the context of metabolic control, in the maturation of polypeptide precursors [2,3], in the immune response through the production of peptides presented on the cell surface by the major histocompatibility complex class I, and also in proliferation and programmed cell death [4]. To date, lysosomes, calpain, caspases and the ubiquitin-proteasome system are the four main intracellular proteolytic systems [5].…”
Section: Introductionmentioning
confidence: 99%